2022
DOI: 10.3390/healthcare10091719
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Narcissism and Problematic Social Networking Sites Use: Focusing the Lens on Specific Motivations for Social Networking Sites Use

Abstract: Research highlighted that Problematic Social Networking Sites Use (PSNSU) and vulnerable narcissism are associated. However, the mechanisms underlying this relationship are still unclear. The present study aimed to test the mediating role of motives for social networking sites (SNSs) use between vulnerable narcissism and five symptoms of PSNSU (i.e., preference for online social interactions, mood regulation, cognitive preoccupation, compulsive use, and negative outcomes) in a sole model. Self-report questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Furthermore, when considered together with the grandiose trait, the personality trait of vulnerable narcissism, (i.e., signaling more significant fluctuations in self-esteem, devaluation of self and withdrawal) was associated with PIU over and beyond the grandiosity trait (i.e., sense of entitlement, inflated sense of self). One might think, therefore, that Internet use has to do with the search for a protected place from perceived difficulties in relationships outside the Web; however, in line with previous research (Casale & Banchi, 2020;Ksinan & Vazsonyi, 2016;Musetti et al, 2022), our findings show that higher feelings of inadequacy and insecurity are associated with greater problems in Internet use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, when considered together with the grandiose trait, the personality trait of vulnerable narcissism, (i.e., signaling more significant fluctuations in self-esteem, devaluation of self and withdrawal) was associated with PIU over and beyond the grandiosity trait (i.e., sense of entitlement, inflated sense of self). One might think, therefore, that Internet use has to do with the search for a protected place from perceived difficulties in relationships outside the Web; however, in line with previous research (Casale & Banchi, 2020;Ksinan & Vazsonyi, 2016;Musetti et al, 2022), our findings show that higher feelings of inadequacy and insecurity are associated with greater problems in Internet use.…”
Section: Discussionsupporting
confidence: 89%
“…As some studies suggested, individuals with grandiose narcissism may use the Internet to promote their self-image. By contrast, individuals with vulnerable narcissistic features may use the Internet to cope with feelings of inadequacy (Ksinan & Vazsonyi, 2016) and, according to others, also a gratification-seeking process (Musetti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Young people believe that Facebook is a good source for information seeking and sharing. Thus, they utilize this platform for information seeking and sharing [65][66][67][68][69][70].…”
Section: Rationale Of Current Studymentioning
confidence: 99%
“…According to the compensatory model of problematic Internet use (Kardefelt-Winther, 2014), motivations for PSNSU represent unfulfilled needs or psychosocial difficulties (Musetti, Grazia, et al, 2022;Musetti et al, 2021). Although PSNSU might lead to negative psychological consequences, the behavior is strengthened through negative reinforcement, as individuals might tend to engage in it in order to relieve negative affect and compensate for the emotional turmoil associated with stressful situations (Billieux et al, 2015;Boursier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%